2008
DOI: 10.1080/01647950808683708
|View full text |Cite
|
Sign up to set email alerts
|

Dorsipes saxicolae, a new species of mite (Acari: Podapolipidae), an ectoparasite of Amara (Pparacelia) saxicola Zimm. (Coleoptera: Carabidae) from Iran

Abstract: 2008) Dorsipes saxicolae, a new species of mite (Acari: Podapolipidae), an ectoparasite of Amara (Pparacelia) saxicola Zimm. (Coleoptera: CarabidaeABSTRACT -Dorsipes saxicolae n. sp. (Acari: Podapolipidae) is described from Amara (Paracelia) saxicota Zimm. (Coleoptera: Carabidae) from northeastern Iran. Dorsipes saxicolae is compared with 4 other species in the inflatus group of Dorsipes Regenfuss. A key to the species is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…and some congeners in platysmae species group are summarised in Table 1. Husband (2000) mentioned that these setae were broken in the types; ** Larval female of D. nigeri is unknown Regenfuss, 1968 Carabus granulatus L. Germany Regenfuss (1968) Russia Eidelberg (1994) Carabus arvensis conciliator Fischer von Waldheim Russia Eidelberg (1994) D. carabi Regenfuss, 1968 Carabus granulatus L. Germany Regenfuss (1968) Belarus Eidelberg (1994) Carabus hortensis L. Belarus Eidelberg (1994) Poland (2011) D. zeelandicae Kurosa & Husband, 2011 Diplocheila zeelandica Redtenbacher Japan Kurosa & Husband (2011) inflatus species group D. inflatus Regenfuss, 1968 Amara equestris (Duftschmid) Germany Regenfuss (1968) D. notopus Regenfuss, 1968 Amara aulica (Panzer) Germany Regenfuss (1968) Switzerland Husband & Dastych (2000) D. curtonoti Amara (Curtonotus) gigantea (Motschulsky) Japan D. amara Amara latior (Kirby) USA D. saxicolae Hajiqanbar & Husband, 2008 Amara (Paracelia) saxicola Zimmermann Iran Hajiqanbar et al (2008) platysmae species group D. platysmae Regenfuss, 1968 Pterostichus niger (Schaller) Germany Regenfuss (1968) Russia (Siberia) Eidelberg (1994) Italy Husband & Dastych (2000) Poland Szczepanska and Magowski (2006) D. adelosiae Regenfuss, 1968 Pterostichus nigrita (Paykull) Germany Regenfuss (1968) Pterostichus macer (Marsham) Russia (Siberia) Eidelberg (1994) D. cryptobius Regenfuss, 1968 Pterostichus nigrita (Paykull) Germany Regenfuss (1968) Siberian Belarus Eidelberg (1994) Pterostichus anthracinus (Illiger) Belarus Eidelberg (1994) Agonum assimile (Paykull) Ukraine (Crimea) Eidelberg (1994) Pterostichus sp. Hungary …”
Section: Remarksmentioning
confidence: 98%
See 1 more Smart Citation
“…and some congeners in platysmae species group are summarised in Table 1. Husband (2000) mentioned that these setae were broken in the types; ** Larval female of D. nigeri is unknown Regenfuss, 1968 Carabus granulatus L. Germany Regenfuss (1968) Russia Eidelberg (1994) Carabus arvensis conciliator Fischer von Waldheim Russia Eidelberg (1994) D. carabi Regenfuss, 1968 Carabus granulatus L. Germany Regenfuss (1968) Belarus Eidelberg (1994) Carabus hortensis L. Belarus Eidelberg (1994) Poland (2011) D. zeelandicae Kurosa & Husband, 2011 Diplocheila zeelandica Redtenbacher Japan Kurosa & Husband (2011) inflatus species group D. inflatus Regenfuss, 1968 Amara equestris (Duftschmid) Germany Regenfuss (1968) D. notopus Regenfuss, 1968 Amara aulica (Panzer) Germany Regenfuss (1968) Switzerland Husband & Dastych (2000) D. curtonoti Amara (Curtonotus) gigantea (Motschulsky) Japan D. amara Amara latior (Kirby) USA D. saxicolae Hajiqanbar & Husband, 2008 Amara (Paracelia) saxicola Zimmermann Iran Hajiqanbar et al (2008) platysmae species group D. platysmae Regenfuss, 1968 Pterostichus niger (Schaller) Germany Regenfuss (1968) Russia (Siberia) Eidelberg (1994) Italy Husband & Dastych (2000) Poland Szczepanska and Magowski (2006) D. adelosiae Regenfuss, 1968 Pterostichus nigrita (Paykull) Germany Regenfuss (1968) Pterostichus macer (Marsham) Russia (Siberia) Eidelberg (1994) D. cryptobius Regenfuss, 1968 Pterostichus nigrita (Paykull) Germany Regenfuss (1968) Siberian Belarus Eidelberg (1994) Pterostichus anthracinus (Illiger) Belarus Eidelberg (1994) Agonum assimile (Paykull) Ukraine (Crimea) Eidelberg (1994) Pterostichus sp. Hungary …”
Section: Remarksmentioning
confidence: 98%
“…However, recent studies have revealed new species and records of all four carabid-associated genera from several parts of Iran (see Hajiqanbar et al, 2007Hajiqanbar et al, , 2008Hajiqanbar & Khoshnevis, 2011;Hajiqanbar & Mortazavi, 2012;Tajodin et al, 2014;Mortazavi et al, 2014). Furthermore, Eidelberg (1994) reported six species from all species groups of Dorsipes from parts of the former USSR, as the closest neighboring regions of Iran.…”
Section: Introductionmentioning
confidence: 94%
“…Japanese species of Dorsipes are: D. curtonoti Kurosa and , D. limnocarabi Husband and Kurosa, 2002, D. yezoensis Husband and Kurosa, 2002 and the species described herein. The expansion of literature involving Dorsipes after 1968 includes the following contributions: Husband and Rack (1991), Eidelberg (1994), Husband (2000), Husband and Dastych (2000), Husband and Kurosa (2002), , , Husband and Weatherby (2005), Husband and Husband (2007), Hajiqanbar et al (2008) and Husband and Husband (2010). The purposes of this paper are to describe the first record of species in the dorsipes group from a host genus other than Carabus, the genus Diplocheila, compare them with five species in the dorsipes group from Japan, Europe and Western North America and present a revised key to species in the dorsipes group.…”
Section: Introductionmentioning
confidence: 99%